Evolution and Benefit Evaluation of Sustainable Urban Energy Interconnection. Issue 1 (October 2020) - Tan, Xue; Jin, Yanming; Zhao, Qiuli; Du, Honglin; Chen, Di
Abstract: Urban energy interconnection is the most important part of energy interconnection, which push forward the transformation and upgrading of urban energy system, and promotes the coordinated development of urban economy, society and environment. This paper summarizes the stylized facts of urban energy interconnection evolution. Then a urban energy interconnection analysis framework is proposed to analyze the logical framework of the energy system from the physical, information, and value layers. Further, this paper proposes a comprehensive indicator system for quantitatively evaluating the degree of coordination between urban development and energy systems, and provides a method for assessing the comprehensive benefits of sustainable urban energy interconnection.